2017
DOI: 10.1038/srep46214
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale comparison of the fine particle removal capacity of urban forests and wetlands

Abstract: As fine particle (FP) pollution is harmful to humans, previous studies have focused on the mechanisms of FP removal by forests. The current study aims to compare the FP removal capacities of urban forests and wetlands on the leaf, canopy, and landscape scales. Water washing and scanning electron microscopy are used to calculate particle accumulation on leaves, and models are used to estimate vegetation collection, sedimentation, and dry deposition. Results showed that, on the leaf scale, forest species are abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Tree species composition significantly affected particulate concentrations, presumably because the dust-removing ability of plants differs significantly by species [43,44]. The variations in particulate retention among tree species in this study were consistent with those found by Liu [12] and Yang [45] and may be explained by variations in morphological characteristics that enable plants to trap particulates (e.g., canopy structure, leaf density, leaf surface roughness, and wax) [16].…”
Section: Individual Functionssupporting
confidence: 78%
“…Tree species composition significantly affected particulate concentrations, presumably because the dust-removing ability of plants differs significantly by species [43,44]. The variations in particulate retention among tree species in this study were consistent with those found by Liu [12] and Yang [45] and may be explained by variations in morphological characteristics that enable plants to trap particulates (e.g., canopy structure, leaf density, leaf surface roughness, and wax) [16].…”
Section: Individual Functionssupporting
confidence: 78%
“…Conifers are well-known to remove more airborne PM than evergreen or deciduous broadleaved species (Sun et al, 2014;Khan and Perlinger, 2017;Zhang Z. et al, 2017). This is partly due to their crown shape, as cone-shaped conifers are commonly more exposed to turbulent air movements than spherical broadleaved trees (Beckett et al, 2000).…”
Section: Structural and Seasonal Influences On Particle Depositionmentioning
confidence: 99%
“…Most of the trees are deciduous and Quercus is the most common tree followed by the Korean Red Pine. Coniferous trees are known to have higher PM2.5 collection capacities than those of deciduous trees (Zhang et al, 2017;Liang et al, 2016). Deciduous trees may have broader leaves that aid in PM2.5 adsorption.…”
Section: Estimation Methodsmentioning
confidence: 99%